Trends in National Spending on HIV/AIDS Prevention and Control in Thailand, 2008 to 2011 - Viriyathorn, Shaheda; Pannoi, Tanavit; Tisayaticom, Kanjana; Vasavid, Chitpranee; Prakongsai, Phusit (Journal of Health Science of Thailand, 2017)
The objective of this study was to estimate the magnitude, sources, activities and beneficiary populations of expenditure on HIV/AIDS during 2008 to 2011. With the application of UNAIDS’ guide on national AIDS spending assessment (NASA) 2009, a two dimensional matrix of financing sources and beneficiary populations by healthcare function was produced. Data were compiled from secondary data on actual expenditure on HIV/AIDS where available from relevant financing agents. Expenditure data from households and non-governmental organizations were excluded from the study. It was found that the total expenditure on HIV/AIDS in Thailand in 2011 was 9,921.63 million baht (153.79 baht per capita), which increased from 6,928.25 million baht in 2008. The total expenditure on HIV/AIDS accounts for 0.09 percent of GDP in 2011, or equivalent to 2.04 percent of total health expenditure. Domestic sources of finance concentrated mostly on care and treatment for HIV infection, accounting for 84.29 percent and 83.93 percent in 2010 and 2011 respectively. International sources covered 41.56 percent of the entire HIV/AIDS expenditure on prevention, whilst spent only 8.98 percent treatment and care. Major beneficiaries of the HIV/AIDS spending were adults and young people (15 years and over) living with HIV, mainly for treatment and care. HIV/AIDS expenditure has increased steadily from 2008-2011. The spending on treatment and care for people living with HIV/AIDS showed a significant upward trend, from 13,010.26 baht per capita in 2008 to 20,594.16 baht in 2011. This was the results of decreasing number of HIV/AIDS cases and increasing cost for second-line antiretroviral drugs due to the high number of patients developing resistance to the first line drugs. The authors recommended that HIV prevention programmes should be strengthened in particular the prevention of new infections as well as prevention of drug resistance to control spending on antiretroviral therapy. Domestic financing should concentrate more on supporting disease prevention; and ensure financial sustainability of the overall HIV/AIDS programmes.